The Role of Non-Governmental Organizations in Social and Educational Support to Achieve Sustainable Development A field Study in Lattakia City (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the role played by Non-Governmental Organizations in social and educational support in Lattakia city to achieve sustainable development from the point of view of its workers. And revealing the differences between the opinions of workers in Non-Governmental Organizations at Lattakia City about their role in social and educational support according to the variables (the number of years of experience in the association, and educational achievement), Adopting the descriptive approach, and the questionnaire was used as a research tool, consisting of (38) phrases to measure the role of Non-Governmental Organizations at Lattakia city in social and educational support to achieve sustainable development, and was applied to a sample of (104) workers in Non-Governmental Organizations in Lattakia city.      The results of the research showed that the role of Non-Governmental Organizations in Lattakia City in social and educational support to achieve sustainable development was mentioned to a medium degree, and the results showed that there were no statistically significant differences about the role of these associations in social and educational support to achieve sustainable development according to the variable of the number of years of experience in the association, and the existence of statistically significant differences according to the variable of educational achievement in favor of university degree holders.      Accordingly, several recommendations were made, the most important of which are: attention to spreading awareness of the importance of the role of Non-Governmental Organizations in community development, monitoring the strengths and weaknesses of Syrian Non-Governmental Organizations so that the association can train them according to their training needs to meet social and educational requirements, and developing the work of Syrian Non-Governmental Organizations to achieve sustainable development goals.